Species and distribution of mantids (Mantodea) from Tolima, Colombia - ARIZA, GLORIA MARÍA; SALAZAR-E., JULIÁN A.; CANAL, NELSON A. (Revista Colombiana de Entomología, 2012)
Species of mantids from the Department of Tolima, Colombia, were identified from specimens collected in the field and from material deposited in the “Museo del Laboratorio de Entomología” from “Universidad del Tolima”. Surveys were carried out in the Coello River Basin; the area was divided into ten sections according to the altitude; two points were chosen in each section and mantids were collected from 100 m2 transects. Each site was surveyed for 45 minutes. In Tolima 22 species of mantids were found, including a possible new species in the genera Acanthops and the new record from Colombia Parastagmatoptera serricornis. Pseudomiopteryx infuscata is confirmed from Colombia. Descriptive figures of oothecae and genitalia of some collected species are shown.